'Vulnerable' Kids Going Country: Children and Young People's Involvement in County Lines Drug Dealing. (April 2020) - Windle, James; Moyle, Leah; Coomber, Ross
This article employs a range of sources to critically explore the role of children and young people in county lines drug dealing, the potential harms they are exposed to and the difficulties of protecting them. As county lines centre upon the movement and exploitation of vulnerable peoples, we utilise the human trafficking literature for further insights into the dynamics of county lines and current policy responses. The article concludes by discussing the challenges of safeguarding young people, particularly that over-worked and under-resourced frontline practitioners can experience difficulties identifying the vulnerability of young people caught up in county lines, particularly beneath their tough exteriors.